Educational expansion and its heterogeneous returns for wage workers - Michael Gebel; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
The paper examines the evolution of returns to education in the West German labour market over the last two decades. During this period, graduates from the period of educational expansion in the sixties and seventies entered the labour market and an upgrading of the skill structure took place. In order to tackle the issues of endogeneity of schooling and its heterogeneous returns we apply two estimation methods: Wooldridge?s (2004) approach that relies on conditional mean independence and Garen?s (1984) control function approach that requires an exclusion restriction. For the population of workers from the GSOEP, we find that both approaches produce estimates of average returns to education that decrease until the late 1990s and increase significantly afterwards. In the observation period, the gender gap in returns to education seems to vanish. Furthermore, we find that the so called ?baby boomer? cohort has the lowest average return to education in young ages. However, this effect disappears when they become older.
Keywords: J31; J24; J21; 330; Educational expansion; correlated random coefficient model; heterogeneous returns to education; conditional mean independence